Comparison of respiratory inductive plethysmography versus head-out plethysmography for anesthetized nonhuman primates in an animal biosafety level 4 facility. (5th December 2016) - Bohannon, J. Kyle; Honko, Anna N.; Reeder, Rebecca J.; Cooper, Kurt; Byrum, Russ; Bollinger, Laura; Kuhn, Jens H.; Wada, Jiro; Qin, Jing; Jahrling, Peter B.; Lackemeyer, Matthew G.
Abstract: For inhalational studies and aerosol exposures to viruses, head-out plethysmography acquisition has been traditionally used for the determination of estimated inhaled dose in anesthetized nonhuman primates prior to or during an aerosol exposure. A pressure drop across a pneumotachograph is measured within a sealed chamber during inspiration/exhalation of the nonhuman primate, generating respiratory values and breathing frequencies. Due to the fluctuation of depth of anesthesia, pre-exposure respiratory values can be variable, leading to less precise and accurate dosing calculations downstream. Although an anesthesia infusion pump may help stabilize the depth of sedation, pumps are difficult to use within a sealed head-out plethysmography chamber. Real-time, head-out plethysmography acquisition could increase precision and accuracy of the measurements, but the bulky equipment needed for head-out plethysmography precludes real-time use inside a Class III biological safety cabinet, where most aerosol exposures occur. However, the respiratory inductive plethysmography (RIP) acquisition method measures the same respiratory parameters by detecting movement of the chest and abdomen during breathing using two elastic bands within the Class III biological safety cabinet. As respiratory values are relayed to a computer for software integration and analysis real-time, adjustment of aerosol exposure duration is based on the depth of sedation of the animal. The objective of this study was to compare values obtained using two methodologies (pre-exposure head-out plethysmography and real-time RIP). Transitioning to RIP technology with real-time acquisition provides more consistent, precise, and accurate aerosol dosing by reducing reported errors in respiratory values from anesthesia variability when using pre-exposure head-out plethysmography acquisition.